2003
DOI: 10.1097/01.ju.0000065592.55499.4e
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Calcium Oxalate to Calcium Phosphate With Recurrent Stone Episodes

Abstract: Our study suggests a strong trend for the conversion of stone disease from calcium oxalate to calcium phosphate containing stones, which could influence the progression and severity of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 5 publications
0
63
1
Order By: Relevance
“…Some data suggest that calcium phosphate stones have increased in prevalence. If true, the reasons are uncertain and have been attributed to treatment with citrate supplements (see below) or adverse effects of extracorporeal shockwave lithotripsy (3,4). Lithotripsy has been hypothesized to lead to defective urinary acidification, but this effect is highly speculative.…”
Section: Overview Of Calcium Phosphate Stonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some data suggest that calcium phosphate stones have increased in prevalence. If true, the reasons are uncertain and have been attributed to treatment with citrate supplements (see below) or adverse effects of extracorporeal shockwave lithotripsy (3,4). Lithotripsy has been hypothesized to lead to defective urinary acidification, but this effect is highly speculative.…”
Section: Overview Of Calcium Phosphate Stonesmentioning
confidence: 99%
“…A higher urine pH distinguishes calcium phosphate stone formers from calcium oxalate stone formers, although there is overlap. At higher urine pH values, monobasic phosphate (H 2 PO 4 2 ) gives up a proton and becomes dibasic phosphate (HPO 4 = ). This species is much more prone to combine with the divalent cation calcium.…”
Section: Defective Renal Tubular Acidificationmentioning
confidence: 99%
“…Calcium phosphate kidney stones include apatite (carbapatite or hydroxyapatite (HAP)), brushite (Bru) and octacalcium phosphate (OCP) with the occurrence rate of apatite, 4-10%; Bru, 2-6%; and octacalcium phosphate, less than 1% (14). A recent study has reported that the occurrence of calcium phosphate containing stones has increased over time (18). Calcium phosphate occurs in stones in several different forms: amorphous calcium phosphate (ACP), HAP,…”
Section: Commentsmentioning
confidence: 99%
“…5 Extra corporeal shock wave lithotripsy may be used to people with kidney stone between 4mm to 2cm in diameter 6 or renal calculi less than 3cm in size. 7,8 ESWL was recommended for some <2 cm. This size limit was recommended because of problems with high treatment failure rates and steinstrase for longer calculi.…”
Section: Introductionmentioning
confidence: 99%